Peran Serta Rumah Sakit Khusus Gigi dan Mulut Selama Masa Pandemi Covid-19 - Novalino Novalino; Wiku Bakti Bawono Adisasmito (Syntax Corporation Indonesia, 2021)
The COVID-19 pandemic, which has occurred for almost 2 years, has infected more than 200 countries in the world, has made hospital conditions change the service strategy provided. Services that are usually provided during normal times, must change conditions starting from screening patients on arrival until the service ends. When referral hospitals are trying to save patients infected with COVID-19, other hospitals, especially dental and oral hospitals, also participate in removing this nation from the grip of the COVID-19 pandemic, although they do not directly treat COVID-19 patients. By using descriptive qualitative research methods, researchers can obtain deeper information from a case study at a special dental and oral hospital, which usually only provides dental services. The purpose of this study was to get an overview of the efforts made by dental and oral hospitals in providing services to the community in an effort to break the chain of transmission of COVID-19. The results obtained are an evaluation of the increase in the number of patients and dental emergency room services, the implementation of tracing and testing for all hospitalians, as well as providing vaccination services, which are things that special dental and oral hospitals can do in participating in taking part and breaking the chain of transmission of COVID-19.